The Impact of Relationship Marketing on Customer Loyalty in a Private Bank - Wahyu, Ferronibah (iBuss Management, 2014)
Customers are the basic requirement for a success business. Where competition is tight, companies will be more intentional about gaining customer loyalty. Customer loyalty is important, because when customers are loyal, they will not even look at oneâs competitors. This change can be through developing good relationships with customers. This research aims to find the impact of relationship marketing on customer loyalty in one of the private banks in Surabaya. It will help the company to maintain customer loyalty as they go beyond their expectations, especially in the banking industry where product innovation cannot be the only strategic weapon to compete and to have a sustainable and profitable business. This research could gather 111 respondents as the sample with a method of random sampling. The data was analysed by using multiple regression analysis. As the results, this researcher found that Relationship marketingâs elements simultaneously have a significant effect on customer loyalty. Furthermore, there are also two elements of relationship marketing which have a significant impact on customer loyalty individually. Namely, trust and competence. Â Keywords: Relationship Marketing, Customer Loyalty, Bank, Service